Seizure after Subdural Hematoma Treated with Combination Western-Korean Medicine - Jae Eun Jeong; You Jung Lee; Yeon Ah Choi; Jang Mi Park; Seung Min Lee; Na Young Jo; Eun Yong Lee; Cham Kyul Lee; Jeong Du Roh (MEDrang Inc., 2021)
Combined Western-Korean medicine treatments were given to a 67-year-old woman with late onset seizures who underwent surgical drainage of a subdural hematoma. Clonazepam and herbal medicine was prescribed. Acupuncture, moxibustion, cupping, chuna, and physical therapy were also performed. The frequency and intensity of seizures was assessed using the Chalfont Seizure Severity Scale. The seizure index score improved from 25 at admission to 0 at discharge. Pain in the right upper extremity reduced from 10 to 0 on the visual analogue scale and muscle strength increased from Grade 3 to 5 in Medical Research Council Scale for the Manual Muscle Test. At the time of hospitalization, the manual muscle strength tests for the affected shoulder, elbow, wrist, and grip strength were 30%, 60%, 10%, 5%, respectively, which improved almost 100% by discharge. Further studies using combined Western-Korean medicine for seizures after strokes are necessary to determine the most effective treatment.